English Language Curriculum at the Secondary Stage Perceptions of Learners and Teachers - Meganathan, Ramanujam (JOURNAL OF INDIAN EDUCATION, 2017)
This paper presents the perceptions of learners and teachers on various aspects of English language education as it is administered in two governmentrun rural schools in the state of Tamil Nadu. Initially, the paper presents the language profiles of learners and their opinions on various aspects of English language education in their schools, followed by the opinions of teachers. Then, it presents two classrooms observed during the study. It attempts to seek answers to the questions: (i) How do learners and teachers perceive English language teaching-learning in a rural setting? (ii) How many languages the learners know and what are the domains of the languages used by them? (iii) Whether teachers’ beliefs and perceptions are influenced by language policy and curriculum reforms? (iv) How is the English language classroom organised to promote language learning?, and (v) Whether the curricular reforms have an impact on the perceptions of learners and teachers?